1988
DOI: 10.1029/rs023i002p00119
|View full text |Cite
|
Sign up to set email alerts
|

A method of estimating horizontal vectors of ionospheric electric field deduced from HF Doppler data

Abstract: A formulation providing time variations of the horizontal electric field in the ionosphere from HF Doppler data is presented. The relationship between the electric field and frequency deviations of ionospherically reflected HF radio waves has been extended from the theory given by Jacobs and Watanabe in 1966. In the present formula, the effect of electron decay due to attachment and/or recombination processes is taken into account for long‐lasting variations in the electric field. The developed formula can pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 17 publications
(8 reference statements)
0
6
0
Order By: Relevance
“…In particular, the production/loss of the ionization is critical to the Doppler frequency for long‐period disturbances [ Tsutsui et al , ]. Nevertheless, the HF Doppler sounder has been proved powerful to detect the long‐period disturbances such as the DP2 and substorms [ Abdu et al , ; Tsutsui et al , ] as well as the short‐period SC, PC, and Pi2.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, the production/loss of the ionization is critical to the Doppler frequency for long‐period disturbances [ Tsutsui et al , ]. Nevertheless, the HF Doppler sounder has been proved powerful to detect the long‐period disturbances such as the DP2 and substorms [ Abdu et al , ; Tsutsui et al , ] as well as the short‐period SC, PC, and Pi2.…”
Section: Discussionmentioning
confidence: 99%
“…The HFD is proportional to the frequency of the radio wave when it is caused by the changes in the reflection height, while inversely proportional when the HFD is caused by changes in the refractive index below the reflection height [ Davies et al , ]. Quite a few papers have shown that the HFD is proportional to the radio frequency for the SC events [ Davies et al , ; Huang et al , ; Kikuchi et al , ; Kikuchi , ], geomagnetic pulsations [ Chan et al , ], and substorms [ Tsutsui et al , ].…”
Section: Observationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The HF Doppler sounders have been widely used to detect the motion of the reflection height of the HF radio signal, providing the ionospheric electric fields of the geomagnetic sudden commencements (SCs), geomagnetic pulsations (Pc5, Pi2), quasiperiodic DP 2 fluctuations, and substorms (Abdu et al, ; Davies et al, ; Huang et al, ; Jayachandran et al, ; Kikuchi, ; Kikuchi et al, , ; Sastri & Subrahmanyam, ; Tsutsui et al, ).…”
Section: Observationsmentioning
confidence: 99%
“…Simpler corrections to the foregoing equations can be obtained by assuming various layer shapes, i.e., for a layer for which the electron density is zero below some reference height and increases linearly with height above the reference height, it can be shown that HF Doppler data have also been used to estimate time variations of the horizontal vectors of the ionospheric electric field at mid-Iatitude by Jacobs and Watanabe (1966) and by Tsutsui et al (1988). Since different frequencies are reflected from different levels in the ionosphere, this can only be accounted for rigorously by ionospheric ray tracing.…”
Section: Hf Doppler Systemsmentioning
confidence: 99%